Endophytic Fungal Community of Tobacco Leaves and Their Potential Role in the Formation of “Cherry-Red” Tobacco - Jiang, Yonglei; Chen, Xing; Zhao, Gaokun; Liu, Jiahong; Xie, Yan; Li, Yong; Gu, Huaguo; Zou, Congming (Frontiers in Microbiology, 2021)
“Cherry-red” tobacco is the superior variant appearing red dapples in cured leaves due to the demethylation of nicotine to nornicotine during maturation and curing. Fungi is known by the capacity of converting nicotine to nornicotine. However, the endophytic fungal community of “cherry-red” tobacco is never reported to our best knowledge. Here we sampled mature leaves from the “cherry-red” and ordinary tobacco at lower, center and upper plant sections, and analyzed the ITS diversity using high-throughput sequencing. Results revealed significantly different fungal community of foliar endophyte in “cherry-red” and ordinary tobacco. In comparison to the ordinary control, higher diversity and co-occurrence network complex were found in “cherry-red” samples, especially in the center and upper leaves, where the red dapples were mainly emerged. More taxa were enriched in the “cherry-red” than ordinary tobacco leaves at all plant sections. Particularly, Aspergillus, some strains of which are reported capable of converting nicotine to nornicotine, was specifically enriched in upper “cherry-red” tobacco leaves, which showed most red dapples after curing. Less robust network structure was detected in the “cherry-red” than ordinary tobacco. The nearest taxon index and β nearest taxon index indicated that the local community structuration of tobacco endophytic fungi mainly driven by deterministic process, while the community turnover among plant sections was stochastic. In conclusion, our study provides the earliest information of endophytic fungal community in “cherry-red” tobacco leaf, and the community diversity, composition and network features synchronous varied with the appearance of red dapples suggested their relationship to the formation of “cherry-red” tobacco.